Uncertainty in action: observing information seeking within the creative processes of scholarly research - T.D. Anderson (Information Research: An International Electronic Journal)
Introduction. This paper discusses the role uncertainty plays in judgments of the meaning and significance of ideas and texts encountered by scholars in the context of their ongoing research activities. Method. Two experienced scholars were observed as part of a two-year ethnographic study of their ongoing research practices. Layered transcriptions of document-by-document discussions, conversations and interviews with informants were analysed for evidence of uncertainty in informants' processes of discovery, evaluation, use and generation of information. Analysis. Three themes are discussed illustrating the dynamic interplay between positive and negative forms of uncertainty: partial relevance, boundaries of understanding and uncertainty tolerance. Results. The uncertainty experienced by informants takes many forms deeply embedded in the interwoven layers of information seeking and use. Positive forms of uncertainty were often, but not exclusively, associated with the informants' explorations within the wider research tasks in which they were engaged. Conclusion. The intricacy of the relationship between what we might consider desirable as opposed to undesirable uncertainty is not easily unravelled. From the searcher's perspective, the interplay between positive and negative forms may be one way of explaining their ability to tolerate challenging encounters within their information and research processes.